Business families in times of crises: The backbone of family firm resilience and continuity. Issue 2 (June 2021) - Calabrò, Andrea; Frank, Hermann; Minichilli, Alessandro; Suess-Reyes, Julia
Abstract: Against the backdrop of the current Covid-19 pandemic and the related world economic crisis, we reflect on the role of the business family as a pivotal resource in family firm crisis management. We discuss how business families respond to the pandemic outbreak and how some accomplish to turn challenges into opportunities and manage to emerge from the crisis even stronger than before. Related to that, we develop a research agenda on crisis management in family firms and the specific role of the business family in this regard. We also introduce the four articles in this special issue which were initially presented at the 3rd International Family Business Research Forum (IFBRF) at WU Vienna in September 2017. All four articles tackle core topics in family business research and practice, including succession, innovation and family governance, which are core elements for building a resilient business family.